The Impact that A New Co-Requisite Model for Entry-Level College Courses is Having on Students’ Success in Mathematics - Padilla-Hernandez, Remigio (My University, 2020)
This study used a quantitative descriptive design and the CIPP model to evaluate the impact a co-requisite model had on students’ passing rates in entry-level college math courses. The co-requisite model has become the alternative to the traditional developmental education sequence, and understanding how it impacts students’ passing rates is important. The study was conducted in a small liberal arts private university in Southwest Georgia. Even though the research about the benefits of the co-requisite model is growing, there are still not enough literature about how this model is affecting students’ passing rates in entry-level math courses at small private universities. The study used archived data from 300 students’ records who took the entry-level math course with and without the co-requisite support lab from Fall 2014 through Fall 2019. The CIPP model was integrated into the research design to aid in the evolution. Four research questions guided the study. A 2 x 2 Factorial ANOVA was used to analyze the data. The results from the Factorial ANOVA data analysis produced one significant result for the main effect gender and two nonsignificant results, one for the main effect co-requisite support lab and one for the interaction effect. However, there was enough evidence to indicate that the co-requisite support lab had an impact on students’ passing rates in the entry-level math course. Results produced by the descriptive statistics revealed that the passing rate for the entry-level math courses was 76.5% (229) and for students who took the lab was 75.3%. In addition, descriptive data analysis showed that women had higher passing rates than men. Overall, the CIPP model, descriptive statistics results and 2 x 2 Factorial ANOVA results were combined to form a bigger picture of the co-requisite program which showed a positive outcome. However, due to the limitations of the study these results cannot be generalized beyond the university’s co-requisite program. Keyword 1: Co-requisite math labs Keyword 2: Co-requisite Keyword 3: Learning support math labs Keyword 4: Supporting math labs
INTRODUCTION 1 -- Barriers, Challenges, and Cost of Developmental Education 2 -- Barriers 2 -- Challenges 3 -- Cost 6 -- Background 7 -- Statement of the Problem 9 -- Theoretical Framework 11 -- Purpose of the Study 12 -- Research Questions 13 -- Definition of Terms 13 -- Significance of the Study 14 -- Limitations 15 -- Delimitation 17 -- Organization of the Study 17 -- Summary 18 -- II. REVIEW OF THE LITERATURE 20 -- The Importance of Placement Practices in Developmental Education 21 -- Current Changes to Developmental Education in Different States 23 -- Community Colleges Helping Developmental Education 24 -- Math Strategies, Support Models, and Does Developmental Math Work? 25 -- Co-requisite Model 31 -- Developmental Math in Georgia 32 -- Private Universities vs Public Universities 35 -- The CIPP Model 36 -- Benefits of the Use of the CIPP Model for Program Evaluation 40 -- Conceptual Map of The CIPP Model 52 -- Summary 52 -- III. METHODOLOGY 55 -- Research Questions 55 -- Research Design 56 -- Validity 59 -- Site Selection and Sampling Procedures 60 -- Site Selection 60 -- Sampling 61 -- Data Collection 64 -- The CIPP Model Data Collection 65 -- Data Analysis 65 -- Testing of Assumptions 66 -- Null Hypotheses 67 -- The CIPP Model 69 -- Summary 69 -- IV. RESULTS 72 -- Introduction 72 -- Demographic Data. 74 -- Resources Put in Place to Help Students in the Co-requisite Program 75 -- University’s Placement Policy for Entry-Level Math Courses 76 -- Testing of Assumptions: Normality and Homogeneity of Variance 77 -- Descriptive Statistics 82 -- ANOVA Results 86 -- Significance of Main Effects 86 -- Interaction Effect 87 -- Additional Test: Pairwise Comparison and Bonferroni 88 -- Summary 89 -- V. SUMMARY AND DISCUSSION. 91 -- Research Questions 92 -- Methodology 92 -- Validity 94 -- Participants 95 -- Data Collection and Analysis 95 -- Summary of Findings 98 -- Discussion of Findings and Related Literature 100 -- The CIPP Model Factors: Context, Input, and Process 100 -- Context 100 -- Input 100 -- Process 103 -- Descriptive Statistics 103 -- 2 x 2 Factorial ANOVA Result and the CIPP Model Factor Product 105 -- Limitations of the Study 108 -- Delimitation of the Study 109 -- Suggestions for Future Research 110 -- Conclusions and Recommendations 111 -- Conclusions 111 -- Recommendations 114 -- REFERENCES 116 -- APPENDIX -- Appendix: Institutional Review Board Protocol Exemption Report 130.
Keywords: Dissertations, Academic--United States; Education, Higher; Educational tests and measurements--Evaluation; Georgia; Mathematics